Factors associated with the detection of atrial fibrillation in patients with embolic stroke of undetermined source - Jae-Han Bae; Jae-Chan Ryu; Sang Hee Ha; Min Soo Cho; Myung-Jin Cha; Jun Young Chang; Dong-Wha Kang; Sun U. Kwon; Jong S. Kim; Bum Joon Kim (BMC Neurology)
Abstract Background Detection of atrial fibrillation (AF) in patients with embolic stroke of undetermined source (ESUS) is important for the secondary prevention of stroke. We investigated the factors associated with the detection of newly diagnosed AF in ESUS patients during follow-up. Methods Patients with acute ischemic stroke classified as ESUS were included. All patients underwent transthoracic echocardiography and Holter to detect the source of embolism. Structural, electrophysiological markers of left atrial cardiopathy (i.e., left atrial enlargement [LAE], non-sustained tachycardia [NSAT]) as well as lesion patterns of ischemic stroke were examined. Implantable loop recorder (ILR) was implanted in selective patients. Sensitivity and positive predictive value analysis was used to assess the predictive value for AF detection. Results Among 312 patients with ESUS, AF was detected in 24 (7.7%) patients during follow-up. Patients with AF had a higher prevalence of LAE, NSAT, and the imaging pattern of confluent plus additional lesions in a single vascular territory. Multivariable analysis showed that ILR implantation (hazards ratio 11.497 [95% confidence interval 3.795–34.818]), LAE (3.204 [1.096–9.370]), NSAT (4.070 [1.378–12.018]), and confluent plus additional lesions (4.977 [1.649–15.019]) were independent predictors of AF detection. The sensitivity of detecting AF in those with LAE, NSAT, or confluent plus additional lesions pattern was 91.7%. The positive predictive value of detecting AF in those with LAE, NSAT and confluent plus additional lesions pattern was 40.0%. Conclusion In conclusion, patients with LAE, NSAT, or confluent plus additional lesions may benefit from ILR monitoring detecting new AF.